Gamers’ acceptance model of Esports – the roles of gratification and service mechanisms - Loh, How Zheng (2023)

(untitled)
The existence of eSports represents a breakthrough sector among the gamers in Malaysia nowadays. However, current development of local eSports is not matured enough to support the growth of gamers’ desires. This had led to lack of understanding and negative perception of non-gaming community towards eSports. Thus, this created the need to conduct this research to investigate what are the factors that influence gamers’ intention to participate in eSports. The hypotheses were developed based on the Technology Acceptance Model (TAM). The Technology Acceptance Model (TAM) was extended by included the influence of gratification and service mechanisms. In addition, pre-test and pilot test were conducted before proceeding to full analysis. The target respondents were the students who are currently joining the video game clubs and societies of universities in Malaysia. A self-administered questionnaire using a quantitative method was distributed to the target respondents for data collection. The results obtained from the sample were analyse using Partial Least Square Structural Equation Modelling (PLS-SEM) for the measurement and structural model. Out of the survey questionnaires collected from the respondents, 453 sets of data were usable for the study. The results indicated that the relationship between gratification, perceived usefulness, perceived ease of use, attitude and intention were supported except the relationship between service mechanisms and perceived usefulness as well as ease of use were found unsupported. Gratification was positively associated with perceived usefulness and ease of use, which in turn affect the attitude and intention of gamers to participate in eSports. Attitude was positively mediated between perceived usefulness, ease of use and intention. The finding of this study is able to provide valuable insights and scholars, policy makers, as well as social development to further improve the eSports sector by increasing the positive awareness about eSports activities. Keywords: Malaysia, eSports, competitive video game, video gamers, gratification, service mechanisms, Technology Acceptance Model (TAM)